Legal adjustment of end-of-service benefits comparative analytical study (Al-Mostansiriyah journal for Arab and international studies, 2026)
Abstract:The end of the work relationship between the worker and the employer entails rights and obligations, and among these rights stipulated in the labor laws for the worker is his entitlement to an end-of-service reward. At the end of service, this reward has raised confusion and doubt in defining its concept, due to the lack of a precise definition for it by the legislator. Therefore, we find that many judicial rulings do not distinguish between the worker’s entitlement to a reward and compensation, and even in many rulings, the worker’s entitlement to the reward is linked to arbitrary dismissal. Although both the right to compensation and compensation for dismissal are independent rights.Keywords: legal nature, distinction of reward, characteristics, provisions, end-of-service reward.